2019
DOI: 10.1038/s41598-019-47279-1
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of weakly interacting bosons in two dimensions: disorder vs lattice geometry effects

Abstract: We investigate the effects of disorder and lattice geometry against localisation phenomena in a weakly interacting ultracold bosonic gas confined in a 2D optical lattice. The behaviour of the quantum fluid is studied at the mean-field level performing computational experiments, as a function of disorder strength for lattices of sizes similar to current experiments. Quantification of localisation, away from the Bose glass phase, was obtained directly from the stationary density profiles through a robust statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 112 publications
(138 reference statements)
0
9
0
Order By: Relevance
“…Several studies have approached the question of interactions in the presence of disorder in cold-atom systems via the Gross-Pitaevskii equation, e.g., [137] in 2D and [138,139,51] in 1D. Reference [51] is particularly interesting, predicting that 1D experiments would not be able to clearly detect Anderson localisation due to the presence of interactions.…”
Section: Interactionsmentioning
confidence: 99%
“…Several studies have approached the question of interactions in the presence of disorder in cold-atom systems via the Gross-Pitaevskii equation, e.g., [137] in 2D and [138,139,51] in 1D. Reference [51] is particularly interesting, predicting that 1D experiments would not be able to clearly detect Anderson localisation due to the presence of interactions.…”
Section: Interactionsmentioning
confidence: 99%
“…Since the prepared initial state is non-stationary, the hyperfine spin populations will evolve under the influence of both, disorder and interactions. Previous analysis of a single BEC component confined in a disordered square in 2D have shown that, in the weakly interacting regime, the net effect of the disorder is to localize the condensate density in bounded regions [19]. As a matter of fact, the size of those bounded regions become shorter and shorter as the amplitude of the disorder strength is increased.…”
Section: Results: Demagnetization Vs Disordermentioning
confidence: 98%
“…Thus, besides the contribution of the harmonic confinement, the potential depth at each point (x, y) is the result of adding/subtracting a random number δ (x, y) to the amplitude of the potential defining the square lattice at zero disorder. Several previous studies have shown that the mean-field approximation describes the main effects of weakly interacting disordered systems [19,[21][22][23][24].…”
Section: Model and Initial State Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite plenty of numerical evidence (cf. [GGCBP19] and the references therein for a recent overview), to the best of our knowledge there has not yet been any direct experimental observation of the localization of ground states under disorder.…”
mentioning
confidence: 99%